The Response of Callus Formation from Tacca Chantrieri Leaves with Various Concentrations of 2,4-D and BAP by In Vitro - Maya Sari; Mayta Novaliza Isda (Universitas Andalas, 2021)
The an annual herbaceous tropical plant which is one of the species of the genus Tacca from the Dioscoreaceae family is Tacca chantrieri. T. chantrieri has a unique inflorescence morphology like that of a bat. The people of Southeast China and Thailand have used by T. chantrieri rhizome as traditional medicine because the methanol extract contains secondary metabolites such as diarylheptanoids, pseudofurostan, withanolide, taccalonolide, and saponins. To maintain its sustainability, it is necessary to propagate T. chantrieri by using in vitro culture techniques such as callus culture. The purpose of this study was to determine the response of T. chantrieri leaf callus formation and to determine the optimal concentration with various concentrations of 2,4-D and BAP in vitro. This study used a completely randomized design consisting of control treatments, 1 and 2 mg L-1 2,4-D and concentrations of 0.5; 1.0; 1.5; 2.0 2,4-D combined with 3 mg L-1 BAP. The observations were made for 60 days after planting. The results showed that the concentration of 1.5 mg L-1 2,4-D + 3 mg L-1 BAP affected the percentage of live explants and the percentage of callus formation by 100% respectively, and the time of callus appeared 18.75 days after planting.